Noninvasive Prenatal Screening Based on Second-Trimester Ultrasonographic Soft Markers in Low-Risk Pregnant Women - Liu, Yunyun; Jing, Xiaosha; Xing, Lingling; Liu, Sha; Liu, Jianlong; Cheng, Jing; Deng, Cechuan; Bai, Ting; Xia, Tianyu; Wei, Xiang; Luo, Yuan; Zhou, Quanfang; et al. (Frontiers in Genetics, 2021)
We aimed to assess the clinical application of noninvasive prenatal screening (NIPS) based on second-trimester ultrasonographic soft markers (USMs) in low-risk pregnant women. Data of pregnant women between April 2015 and December 2019 were retrospectively analyzed. Pregnant women [age at expected date of confinement (EDC) of < 35 years; low risks for trisomy 21 and trisomy 18 based on maternal serum screening; presenting second-trimester USMs (7 types)] who successfully underwent NIPS and had available follow-up information were included in our study. Cases with positive NIPS results were prenatally diagnosed. Subgroup analyses were performed according to the different USMs. NIPS suggested that among a total of 10023 cases, 37 (0.37%) were at high risk of aneuploidy, including 4 T21, 6 trisomy 13, and 27 sex chromosome abnormalities (SCA). Ten cases with aneuploidy (0.10%) were confirmed by prenatal diagnosis, consisting of two T21 and eight SCA. The eight fetuses with SCA consisted of one monosomy X, two XXY, one XXXY, one XXX, one XYY, and two mosaicisms. T21 was detected in one fetus with absent or hypoplastic nasal bone and one fetus with echogenic intracardiac focus (EICF). SCA was detected in five fetuses with EICF, two fetuses with multiple soft markers, and one fetus with echogenic bowel. The positive rate of chromosomal aneuploidy was significantly higher in fetuses with absent or hypoplastic nasal bone (6.25% vs. 0.10%, p=0.017), echogenic bowel (3.7% vs. 0.10%, p=0.029), and multiple soft markers (0.678% vs. 0.10%, p=0.045) than in the total fetuses. The positive predictive values (PPVs) of NIPS in these three groups were 100%, 50%, and 100%, respectively. EICF accounted for 93.25% (9346/10023) of the study population, whereas the PPV of NIPS was only 20%. NIPS is an advanced screening test for low-risk pregnant women. In the 10,023 pregnant women sampled, SCA were more common than autosomal trisomy, and EICF was the most frequent USM but the least predictive aneuploidy. Further aneuploidy evaluation is suggested for low-risk pregnant women whose ultrasound indicates absent or hypoplastic nasal bone, echogenic bowel, or multiple soft markers. NIPS can serve as a second-line complementary screening for these women.